Phytochemical, Antinutrients, Food Toxicants Analysis and Comparative Efficacy of Methanol Extracts of Selected Vegetables of Adamawa State Nigeria on the Haematological Parameters of Alloxan Induced Diabetic Rats - Ngozi, Nwankwo Rita; Ene, Ocheola-Oki Joyce; Tunrayo, Monsurat Moshod (Journal of Food Sciences, 2021)
Purpose: Phytochemicals present in vegetables has been associated with the health potentials of leafy vegetables. Diabetes has been implicated with increased oxidative stress leading to alteration of haematological parameters among other complications. This study investigated the phytochemicals, antinutrients and toxicants contents of methanol extracts of Hibiscus cannabinus, Adansonia digitata, Sesamum indicum and Cassia tora leaves and compared the effect of their leaves extract on some haematological parameters of alloxan - induced diabetic rats using standard methods of analysis. Methodology: Fifty-five (55) male albino rats weighing 120 - 150g divided into 11 groups of five rats each were used. One diabetic untreated rat group, one diabetic group treated with standard drug ,8 diabetic groups treated with graded doses of the vegetable extracts and one normal group as control. All the groups received water and feed ad libitum together with their various treatments for 23 days. At the end of the experiment, blood was taken from the rats for determination of PCV, Hb, WBC, and RBC. ANOVA was used to separate the means of all the data collected with significance at p< 0.05 using Statistical Package for Scientist and Engineers (SPSE) version 9.1. Results: Results showed reasonable levels of phytochemicals, antinutrient and toxicants levels within WHO safe limits. Results of animal studies showed that administration of 500mg of Hibiscus cannabinus leaf extract increased the PCV, HB, WBC and RBC of diabetic rats more than all the other vegetable extracts (p<0.05). It also improved the WBC and RBC better than standard drug. This shows that Hibiscus cannabinus leaf extract might improve some haematological parameters associated with diabetes mellitus, however its inhibitory effect on higher dose raised concern for further investigation. Unique contribution to theory, practice and policy: Hibiscus cannabinus leaf extract could be used in the dietary management of haematological abnormalities associated with the pathophysiology of diabetes mellitus by health care systems